Prospects for The Use of Nanotechnology for The Manufacture of Optical Meta-Materials. - D. Volpyan, O.; I. Kuzmichev., A.; A. Obod, Yu.; S. Sigov, A. (International Journal of Engineering and Technology, 2018)
Nanotechnology methods for obtaining 2D and 3D meta-materials are considered. The main attention is paid to the methods of forming submicron and nanometer structures using nanotechnology methods, first of all laser methods. It is shown that these technological methods, being planar and scalable, are promising for use in industrial optical production due to their potentially high productivity and low cost compared to many other methods of nanotechnology, in particular, with electronic lithography and processing with focused ion beams.Â Â